Islamic Legal Approach in Preventing Women's Involvement in Spreading Hoaxes on Social Media - Hanani, Silfia; Nelmaya, Nelmaya; Ulya, Zakiyah; Aldian, Elsa; Mohd Noor, Ahmad Yunus bin; Rahmana, Sitto (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This article discusses preventing women from being involved in hoaxes on social media using an Islamic legal approach because women are one of the groups that are vulnerable to being exposed to and spreading hoaxes on social media. This research aims to find out how to prevent women from being involved with Islamic law but with an Islamic legal approach. Data was collected with documentation related to analyses by Islamic law experts and the media. Apart from that, interviews were also conducted with female journalists about women's involvement in social media and how to anticipate it, then it was analyzed using a reduction process, presented, and concluded. The results of the research show that the Islamic legal approach can be used as a basis for preventing women from committing hoaxes on social media, if the principles of Islamic law in those media are implemented, among these principles are tabayun, responsibility and always adhering to stick of caution.